The Influential Factors In Purchasing Goods In Convenience Stores: The Cases Of Alfamart And Indomaret In Jakarta - Darmayanti, Dahlia; Halim, Daniel (AIBPM Publisher, 2023)
The aim of this study is to examine the factors that cause Indonesian consumers to purchase products in convenience stores. This study investigates the influential factors such as social media reviews, brand satisfaction, service operations, and price promotions toward customer satisfaction that leads to consumers’ intentions to repeat buying in convenience stores. The survey questionnaires were distributed online. There were 117 respondents who lived in Jakarta, Indonesia, as the valid respondents. The research hypotheses were tested using SEM-PLS. The findings revealed that brand satisfaction and service operations influence customer satisfaction. Also, customer satisfaction is an influential factor that drives customers to engage in repeat purchases in convenience stores. Meanwhile, social media reviews and price promotions do not influence customer satisfaction in convenience stores. The findings give insights into the factors that influence Indonesian consumers’ behavior towards customer satisfaction that leads them to do repeat buying.